Mainstreaming the Existence of Persons with Disabilities as Development Subjects in Sidoharjo Village - Saputra, Wahyu Dwi; Hanung, Gembong (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2023)
People with disabilities are a socially, economically and politically vulnerable group. Even though their existence has been recognized in global norms such as the Sustainable Development Goals (SDGs), their role in development is still often perpetuated as objects rather than subjects of development. This study aims to understand how far the SDGs manifested in the "Inclusion Village" program and other government programs are able to represent the actual needs of persons with disabilities in Sidoharjo Village, Polanharjo, Klaten. Data obtained through qualitative interviews with five persons with disabilities in Sidoharjo Village show that there is indeed a gap between the local context and the global standards of the SDGs. This means that various programs based on inclusivity are still not understood and their impact is not felt by persons with disabilities. The findings in this research indicate that people with disabilities in Sidoharjo Village have not been well-placed as subjects of development. Eventually, there are unfulfilled rights in regard to health, education, welfare and equality services.